Kjellander + Sj$1'Xe(Berg architects /s - Lauri, Tomas; Ibelings, Hans.; Kjellander + Sjoberg (Stockholm : Arvinius Forlag, 2012)
From Arvinius's resplendent series on Nordic architecture comes this photo-packed volume on forward thinking Stockholm-based firm Kjellander + Sjoberg. Since 1988, the practice, led by Stefan Sjoberg and Ola Kjellander, has created a unique minimalist modern aesthetic, playing with shapes and scale, geometry and balance: among their most exciting designs are their internationally famous prefabricated vacation modules, little miracles of architecture in only 160 square feet. Their designs have proven both durable and beautiful, rejecting trendy approaches yet full of color and life.''Kjellander + Sjoberg let architecture be what it should be,'' says Hans Ibelings in one of the book's thought-provoking essays.
Keywords: Kjellander + Sjoberg; Architectural firms -- Sweden; Architecture -- Sweden -- 21st century